1989
DOI: 10.1111/j.1476-5381.1989.tb11851.x
|View full text |Cite
|
Sign up to set email alerts
|

α2‐Adrenoceptor agonists enhance responses to certain other vasoconstrictor agonists in the rat tail artery

Abstract: 1 The effects of the a2-adrenoceptor agonists clonidine, rilmenidine, TL99 and UK14304 on the vasoconstrictor response to sympathetic nerve stimulation and on the concentration-response curves to noradrenaline and phenylephrine were compared in two isolated, perfused vascular tissues: the rat tail artery (which has both postjunctional al-and a2-adrenoceptors), and the rabbit ear artery (in which only cx-adrenoceptors are present postjunctionally). 2 In the rabbit ear artery, the first observable effect of a2-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…It has previously been suggested that, in certain vascular beds, simultaneous activation of l-and M2-adrenoceptors is required before the responses to a2-adrenoceptor stimulation are observed, e.g. in the rabbit saphenous artery (Dunn et al, 1991b) and rat tail artery (Xiao & Rand, 1989). It is likely, therefore, that such interactions may involve complex facilitatory interactions between alr-and M2-adrenoceptor-induced calcium ion channel activation and membrane potential changes.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been suggested that, in certain vascular beds, simultaneous activation of l-and M2-adrenoceptors is required before the responses to a2-adrenoceptor stimulation are observed, e.g. in the rabbit saphenous artery (Dunn et al, 1991b) and rat tail artery (Xiao & Rand, 1989). It is likely, therefore, that such interactions may involve complex facilitatory interactions between alr-and M2-adrenoceptor-induced calcium ion channel activation and membrane potential changes.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-HT receptor is of the 5-HT 2 receptor class 21 (supported by inhibition of 5-HT-induced contraction by the 5-HT 2 receptor antagonist LY53857), the ET-1 receptor is an ET A receptor, 22 and the ␣-adrenergic receptor is a mixture of ␣ 1 -and ␣ 2 -adrenergic receptors. 23,24 All 3 classes of receptors activate similar, classic signaling pathways (plasma membrane calcium channels and phospholipase C), and all receptors have recently been identified as being able to activate the Erk MAPK pathway in vascular smooth muscle. Several investigators have demonstrated that Erk MAPK can phosphorylate caldesmon and, in doing so, release the calmodulin-mediated inhibition of actinomyosin ATPase and thereby promote smooth muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the postjunctional a2-adrenoceptors not only causes a direct contractile action but also en hances the responses to various contractile agents (5,18,19). Therefore, it is likely that, like KT-611, the drugs which have an antago nistic action to both postjunctional a 1 and a2 adrenoceptors may become more beneficial for the control of adrenergic responses in blood vessels and other tissues.…”
Section: Discussionmentioning
confidence: 99%